Characterization and Anticancer Activity from Gaharu (Aquilaria malaccensis) Stem Bark Extract - Tarso Rudiana; Elda Suci Yala Merru; Hendrawati Hendrawati; Dede Sukandar (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
Aquilaria malaccensis is a plant species from the Thymeleaceae family. A. malaccensis contains secondary metabolites of phenolic groups, namely benzophenone, chromone, coumarin, xanthone, and flavonoids with various biological activities such as antioxidants and anticancer. This study aims to determine the potential of A. malaccensis stem bark extract as an anticancer and to determine the characteristics of secondary metabolite compounds contained in A. malaccensis stem bark extract. Extraction of the stem bark of A. malaccensis by maceration method in stages using n-hexane, ethyl acetate and methanol as solvents. The anticancer activity test used the microculture tetrazolium (MTT) assay against Murine Leukemia P-388 cells. Compound separation using thin layer chromatograph (TLC) and gravity column chromatography (CC) methods. Determination of chemical compounds using liquid chromatography mass spectroscopy/mass spectroscopy (LCMS/MS). The extracts of n-hexane, ethyl acetate, and methanol each had anticancer activity which was classified as active with an IC50 value of 20.64, 26.61, and 14.49 µg/mL. Based on the results of separation and identification of compounds in methanol extract with TLC, CC, and LCMS/MS, methanol extract contains acetaminophen, aminosamptothesin, isophorone, diethyl phthalate, 3-hydroxy-6H-benzochromen-6-one, isolongifolenic, 2-(2-phenethyl) chromone, 4′,7-dihydroxy-2′,5-dimethoxyisoflavone, 4-hydroxy-3-(1-phenylpropyl)-2H-chromone-2-one; 6-methylchromone-2-carboxylic acid; 3,4-dimethyl-2- phenylmorpholine; and β-calacoren compounds.